Characterization and treatment of thoracic duct obstruction in patients with lymphatic flow disorders. Issue 5 (6th March 2023) - Srinivasan, Abhay; Smith, Chris; Krishnamurthy, Ganesh; Escobar, Fernando; Biko, David; Dori, Yoav
Abstract: Purpose: The contribution of thoracic duct obstruction to lymphatic flow disorders has not been well‐characterized. We describe imaging findings, interventions, and outcomes in patients with suspected duct obstruction by imaging or a lympho‐venous pressure gradient (LVPG). Materials and Methods: Clinical, imaging, and interventional data, including the LVPG, of patients with flow disorders and imaging features of duct obstruction who underwent lymphatic intervention were retrospectively reviewed, collated, and analyzed with descriptive statistics. Results: Eleven patients were found to have obstruction, median age 10.4 years (interquartile range: 8–14.9 years). Pleural effusions were seen in 8/11 (72%), ascites in 8/11 (72%), both in 5/11 (45%), and protein‐losing enteropathy in 5 (45%). Eight patients (72%) had congenital heart disease. The most common site of obstruction was at the duct outlet in 7/11 patients (64%). Obstruction was secondary to extrinsic compression or ligation 4 patients (36%). Nine patients (82%) underwent interventions, with balloon dilation in 7/9 (78%), massive lymphatic malformation drainage and sclerotherapy in 1, and lympho‐venous anastomosis in 1. There was resolution of symptoms in 7/9 (78% who underwent intervention, with worsening in 1 patient and no change in 1. In these patients, preprocedure mean LVPG was 7.9 ± 5.7 mmHg and postprocedure gradient was 1.6 ± 1.9 mmHg ( p = 0.014). Five patients in this series underwent intervention solely to alleviate duct obstruction and in 4/5 (80%) this led to resolution of symptoms ( p = 0.05). Conclusion: Duct obstruction may be seen in lymphatic flow disorders and can occur from intrinsic and extrinsic causes. Stenosis at the outlet was most common. Obstruction can be demonstrated by an elevated LVPG, and interventions to alleviate the obstruction can be beneficial. Highlights: Key Finding: Duct obstruction can be seen in lymphatic flow disorders and can be characterized by lymphangiography and measurement of the ductal pressure gradient. Patients can benefit from intervention to relieve the obstruction. Importance: Thoracic duct obstruction is a yet undescribed entity that can contribute to symptoms of lymphatic flow disorders. The causes of duct obstruction require further description, but intrinsic obstruction at the duct outlet may be common.